2022
DOI: 10.1108/ijis-05-2022-0093
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life in an urban innovation ecosystem: analyzing talents’ perception in Southern Brazil

Abstract: Purpose Talented people with interpersonal skills and competencies are pivotal for creating knowledge, innovation and organizational effectiveness, contributing to local development. In this regard, the quality of life is a critical factor in attracting and retaining talented people in any region. This study aims to analyze talents’ perception of the quality of life in an urban innovation ecosystem. This study considers talents to be the students from Science, Technology, Engineering and Mathematics programs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…(2020) concluded that social vulnerability harmed ULQ, while Maclean and Salama (2019) found that cultural heritage sites were important for enhancing ULQ. They suggested that urban planners prioritize the creation of cultural amenities to improve ULQ. Other Factors: Additionally, some studies have examined the impact of other factors on ULQ, including housing (Khaef and Zebardast, 2016; Pan et al ., 2018; Ruengtam, 2017), health (Barreira et al ., 2021; Patil and Sharma, 2022), smart city technologies (Adhikari and Roy, 2021; Al-Qawasmi et al ., 2021; Foguesatto et al ., 2022) and safety and security (Alsaid, 2015; Mamuye and Gotu, 2015). In conclusion, ULQ and urban spaces are important topics extensively studied in recent years.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) concluded that social vulnerability harmed ULQ, while Maclean and Salama (2019) found that cultural heritage sites were important for enhancing ULQ. They suggested that urban planners prioritize the creation of cultural amenities to improve ULQ. Other Factors: Additionally, some studies have examined the impact of other factors on ULQ, including housing (Khaef and Zebardast, 2016; Pan et al ., 2018; Ruengtam, 2017), health (Barreira et al ., 2021; Patil and Sharma, 2022), smart city technologies (Adhikari and Roy, 2021; Al-Qawasmi et al ., 2021; Foguesatto et al ., 2022) and safety and security (Alsaid, 2015; Mamuye and Gotu, 2015). In conclusion, ULQ and urban spaces are important topics extensively studied in recent years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other Factors: Additionally, some studies have examined the impact of other factors on ULQ, including housing (Khaef and Zebardast, 2016; Pan et al ., 2018; Ruengtam, 2017), health (Barreira et al ., 2021; Patil and Sharma, 2022), smart city technologies (Adhikari and Roy, 2021; Al-Qawasmi et al ., 2021; Foguesatto et al ., 2022) and safety and security (Alsaid, 2015; Mamuye and Gotu, 2015). In conclusion, ULQ and urban spaces are important topics extensively studied in recent years.…”
Section: Literature Reviewmentioning
confidence: 99%